Avian Leukosis Virus Subgroup J Attenuates Type I Interferon Production Through Blocking IκB Phosphorylation - Lin, Wencheng; Xu, Zhouyi; Yan, Yiming; Zhang, Huanmin; Li, Hongxin; Chen, Weiguo; Chen, Feng; Xie, Qingmei (Frontiers in Microbiology, 2018)
Avian leukosis virus subgroup J (ALV-J) is an oncogenic retrovirus that causes immunosuppression and enhances susceptibility to secondary infection, resulting in great economic losses. Although ALV-J-induced immunosuppression has been well established, the underlying molecular mechanism for such induction is still unclear. Here, we report that the inhibitory effect of ALV-J infection on type I interferon expression is associated with the down-regulation of transcriptional regulator NF-κB in host cells. We found that ALV-J possess the inhibitory effect on type I interferon production in HD11 cells and that ALV-J causes the up-regulation of IκBα and down-regulation of NF-κB p65, and that ALV-J blocks the phosphorylation of IκB on Ser32/36 amino acid residues. Collectively, our findings provide insights into the pathogenesis of ALV-J.